Alter und Ursprung des Rinderhirtennomadismus in Afrika - Gabriel, Baldur (ERDKUNDE, 2002)
The author assembles several arguments for his view that the origin of nomadic cattle pastoralism is to be located in the central or eastern Sahara at a very early date (about 10,000 B.P.?): Faunal relics of domesticated cattle from the eastern Sahara belong to the oldest ones in the world. Indeed, the determination of the quality domesticated being controversial. Neolithic cattle pastoralism in Northern Africa/Sahara is documented by a great number of various rock art. Their age is, however, in dispute. Abundant neolithic fireplaces (Steinplätze) are widely distributed all over the Sahara. They are interpreted as being the camp-fires of nomadic cattle herders. They grant a chronological and spatial analysis though their cultural relations still rest problematic. Today, nomadic cattle pastoralism is restricted to the African continent. There are no historic or prehistoric predecessors elsewhere. The remaining Old World nomadic pastoralism is based mostly on other species of domestic animals. Nevertheless, early domestic cattle is known from Near East and from Southern Europe, too. The African continent exhibits a chronological incline of cattle pastoralism from North to South, arriving in South Africa not previous to 2000 B.P. During the millennia in question the Sahara proved to be a savanna-like landscape with good ecological conditions for the development of such an economic strategy of land utilization and of exploitation of natural resources. Modern genetic results indicate a very early separation (>22,000 B.P.) of the African cattle breed from their Eurasian relatives. Linguistic arguments point to the Sahara as a centre for early cattle-breeding.